Cortos sin cortes: A didactic sequence for the use of short films as an instrument to develop listening skills (2022)
Teachers and other experts in education are constantly looking for new techniques, methodologies and resources that help innovate in language teaching to make it as effective and motivating as possible, both for students and teachers. The use of short films in the classroom is not something new, since many teachers have been using them for a long time. However, their possibilities as a teaching resource to foster listening skills have not been fully exploited yet. This project aims at developing a didactic sequence for the use of short films as a resource to develop listening skills as well as exploring the opportunities that short films can offer to the world of education and to boost a wider use of them in educational contexts. Besides, it is important to take into account all the necessary elements that are involved in the development of the didactic sequence such as materials ( audios, songs, dynamic and physical games, short films, clips, and others) and knowledge required, as well as the facility to have access to the population and infrastructure required for the implementation of the authentic material